2013
DOI: 10.1038/cr.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

A current perspective of autophagosome biogenesis

Abstract: Autophagy is a bulk degradation system induced by cellular stresses such as nutrient starvation. Its function relies on the formation of double-membrane vesicles called autophagosomes. Unlike other organelles that appear to stably exist in the cell, autophagosomes are formed on demand, and once their formation is initiated, it proceeds surprisingly rapidly. How and where this dynamic autophagosome formation takes place has been a long-standing question, but the discovery of Atg proteins in the 1990's significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
252
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(265 citation statements)
references
References 106 publications
3
252
0
2
Order By: Relevance
“…2,3,46,47,56 Regulation of autophagy: The core molecular machinery engaged in autophagosome formation, as well as the signaling pathways that stimulate autophagy have been reviewed in detail elsewhere. [57][58][59][60][61] Fifteen autophagy-related (ATG) proteins constitute the core machinery of autophagosome formation. 59 In mammalian cells, these ATG proteins are recruited to form a phagophore, or isolation membrane, which subsequently elongates to form the autophagosome (Figure 2).…”
Section: Autophagy and Ciliummentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,46,47,56 Regulation of autophagy: The core molecular machinery engaged in autophagosome formation, as well as the signaling pathways that stimulate autophagy have been reviewed in detail elsewhere. [57][58][59][60][61] Fifteen autophagy-related (ATG) proteins constitute the core machinery of autophagosome formation. 59 In mammalian cells, these ATG proteins are recruited to form a phagophore, or isolation membrane, which subsequently elongates to form the autophagosome (Figure 2).…”
Section: Autophagy and Ciliummentioning
confidence: 99%
“…Recent studies have shown that phagophore elongation takes place at the endoplasmic reticulum in a structure called the omegasome characterized by the presence of the phosphatidylinositol 3-phosphate binding protein DFCP1. 58,61,62 In addition, other membrane sources also contribute to the biogenesis of the autophagosome, including those of the endosomes and the Golgi apparatus, the contact site between the endoplasmic reticulum and mitochondria, endoplasmic reticulum transition elements, and the plasma membrane (for recent reviews, Lamb et al 58 ; Shibutani and Yoshimori 61 ; and Puri et al 63 ). Each functional module from the initiation of the autophagosome formation to the elongation/closure step involves different ATG proteins.…”
Section: Autophagy and Ciliummentioning
confidence: 99%
See 1 more Smart Citation
“…23,26 Activation of the ULK1 complex results in the translocation of the BECN1-containing class III phosphatidylinositol 3-kinase (PtdIns3K) complex to the assembly site of a phagophore 27 to promote the generation of phosphatidylinositol-3-phosphate (PtdIns3P), which is involved in recruiting a number of ATG proteins. 28,29 There are multiple PtdIns3K complexes that, in addition to BECN1, include combinations of the proteins ATG14, SH3GLB1/Bif-1 (SH3-domain GRB2-like endophilin B1), UVRAG (UV radiation resistance associated), and AMBRA1 (autophagy/Beclin 1 regulator 1), as well as the negative regulator KIAA0226/Rubicon; BECN1 can also be prevented from binding the complex due to its interaction with BCL2 (B-cell CLL/lymphoma 2). [30][31][32][33][34] The elongation and expansion of the phagophore involves 2 ubiquitin-like conjugation systems, the ATG12-ATG5-ATG16L1 conjugation system, and the microtubule-associated protein 1 light chain 3 (LC3; Atg8 homolog) conjugation system.…”
Section: The Process and Regulation Of Autophagymentioning
confidence: 99%
“…These proteins can be grouped into various complexes based on their functions: the ULK1 kinase complex, the ATG9-ATG2-WIPI1/Atg18 complex, PIK3C3/Vps34-BECN1-PIK3R4/p150/Vps15 complex, and 2 ubiquitin-like conjugation systems, which include the ATG12-ATG5 and LC3/GABARAP proteins. [5][6][7] In mammalian cells, under autophagy-stimulating conditions, the ULK1 complex (mainly composed of ULK1, ATG13, ATG101 and RB1CC1/FIP200) undergoes a series of phosphorylation/dephosphorylation events, which lead to the activation of this complex and the initiation of autophagy. 8 After the initiation step, a cup-shaped, primary double-membrane structure, the phagophore, is gradually formed.…”
Section: The Process Of Autophagy and Its Machinerymentioning
confidence: 99%